Student collaboration skills post-implementation of the WE-ARe model - Romi Adiansyah; Astuti Muh. Amin; Siti Darwa Suryani (Research and Development in Education (RaDEn), 2024)
Collaboration skills are fundamental to helping students face challenges in education and work. However, there is limited research on students’ collaboration skills, particularly using a specific model. This present study aims to analyze the influence of the Warm-up, Exploring, Argumentation, Resume (WE-ARe) model on students' collaboration skills. We employed a quasi-experimental design with a Pre-test and Post-test Group Design. The sample was Islamic High School of Eleventh Grade Natural Science Program-2, totalling 28 people. The data was obtained through questionnaires, observation, and interview questions with instruments validated by experts and empirical processes. The t-test results show that the WE-ARe learning model significantly influences students’ collaboration skills with a t-count of 47.753 (sig. 0.000). This finding indicates that the research hypothesis concerning differences in students' pre-test and post-test collaboration skills in the WE-ARe learning model was accepted, signifying that the WE-ARe learning model improves students’ collaboration skills. It can be concluded that the WE-ARe model influences students' collaboration skills. This finding implies that the WE-ARe model can be an alternative innovative model in accommodating students’ collaboration skills in learning.